Evaluation of attributes and quality Indices in nursery plants for successful reforestation in Pinar del Río, Cuba: Systematic review: Protección del Ambiente - García-Decoro, Samantha (2024)
The reforestation process is one of the most complex tasks for foresters since there are several factors that limit success, one of them has to do with the quality of the material to be planted. Hence, every day it is more important to guide studies that facilitate understanding the adaptation of plants to the site and the establishment of highly productive plantations, based on the production of quality plants in nurseries. The objective of this work was to evaluate the attributes and quality indices of the most appropriate plants in forest nurseries, through a systematic review, as a contribution to reforestation programs in the province of Pinar del Río, Cuba. The methodology sought relevant data from the review of reliable sources related to the issue of plant quality in the nursery. The results reported the need to diagnose the quality of a plant in the nursery through the combination of morphological and physiological parameters that allow us to better understand the functioning of the plant and guarantee its response to the planting site. It was found that more than 90% of the studies expressed a positive relationship between the diameter of the plant in the nursery and the growth after planting, making these parameters a high priority for decision making regarding the quality of the forest plant, which would facilitate greater growth, survival and development in plantation conditions.